Overtime Regulation and Contract Workers: A Philosophical Reflection on Justice and Legal Protection in Indonesian Labour Practice - Siti Fara Maulidiyah Rachman; Muh. Ali Masnun; Widari Azhar Syaputri (Universitas Negeri Surabaya, 2025)
The implementation of overtime working hours and the payment of overtime wages for workers employed under Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu/PKWT), based on the prevailing laws and regulations, namely Law Number 11 of 2020 on Job Creation and Government Regulation Number 35 of 2021, provides that PKWT workers are entitled to overtime working hours and overtime wages in accordance with statutory provisions. However, in practice, cases are still found in which PKWT workers are required to work beyond the stipulated working hour limits without receiving the overtime wage compensation to which they are legally entitled. This situation can be observed in certain companies, which become the focus of this study in relation to the implementation of legal protection for workers who work beyond the prescribed working hours. This research aims to examine and analyze the implementation of overtime working hour provisions and the payment of overtime wages for workers employed under Fixed-Term Employment Agreements (PKWT). To achieve this objective, the study employs empirical legal research using a juridical-empirical approach, also known as a sociology of law approach, supported by field data obtained through a case study of companies employing PKWT workers. The results of the study indicate that many companies have not yet fully implemented overtime provisions in accordance with applicable regulations, both in terms of working hour limits and the provision of overtime wage compensation.